Bulk Rashba Spin Splitting and Dirac Surface State in p‐Type (Bi0.9Sb0.1)2Se3 Single Crystal. Issue 4 (5th January 2022) - Ghose, Pradeepta Kumar; Bandyopadhyay, Subhadeep; Dalui, Tamal Kumar; Tseng, Jochi; Dey, Jayjit Kumar; Tomar, Ruchi; Chakraverty, Suvankar; Majumdar, Subham; Dasgupta, Indra; Giri, Saurav
Abstract : Herein, bulk Rashba spin splitting (RSS) and associated Dirac surface state in (Bi0.9 Sb0.1 )2 Se3, exhibiting dominant p ‐type conductivity is reported. It is argued that the synchrotron diffraction studies that origin of the bulk RSS is due to a structural transition to a non‐centrosymmetric R 3 m phase below ≈30 K. The Shubnikov–de Haas–Van oscillations are observed in the magnetoresistance curves at low temperature. The extrapolation of the linear plots for both the | | and ⊥ component in the Landau level fan diagram meet at n = 0.40(6) for 1/ H = 0, which is close to n = 0.5 is recommended for the Dirac particles. The magnetization results at low temperature exhibit substantial orbital magnetization consistent with the bulk RSS. The bulk RSS and Dirac surface states are confirmed by the first‐principles density functional theory calculations. The coexistence of orbital magnetism, bulk RSS, and Dirac surface state is unique for p ‐type (Bi0.9 Sb0.1 )2 Se3, making it an ideal candidate for spintronic applications. Abstract : Experimental probes and first‐principles density functional theory reveal the coexistence of bulk Rashba spin splitting (RSS) and Dirac surface state in p‐ doped (Bi0.9 Sb0.1 )2 Se3 single crystals. A transition to a low‐temperature noncentrosymmetric structure (R3m) leads to RSS. Analysis of SdH oscillations confirms the conducting Dirac surface state. Simultaneous occurrence of RSS and Dirac surface state is promising for spintronic applications.